Modern Pesantren Leadership Based on Internalisation of Pancajiwa - Ririn Inayatul Mahfudhoh; M. Yunus Abu Bakar; Ah. Zakki Fuad (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to find out how the implementation of leadership in modern cottages, especially about the concept of Modern Pesantren according to KH. Imam Zarkasyi, the dynamics of leadership, and the internalization of pancajiwa in the framework of the regeneration carried out in the modern cottage of Darussalam Gontor. With literature studies using literary sources both primary and secondary, this study describes that according to KH. Imam Zarkasyi, the concept of Modern Pesantren has 3 aspects, namely first modern in the field of curriculum as the core of the educational process in pesantren, second modern in the field of pesantren management as a system that regulates the entire series of educational processes, and third modern in the tradition of pesantren where all components in pesantren must have the same goal. Then the leadership at Pondok Modern Darussalam Gontch was run by KH. Imam Zarkasyi is visionary and progressive because he is oriented towards the objectives of Pesantren education by prioritizing discipline and uswah Hashanah, this is one of which is realized by internalizing pancajiwa as a philosophy of Modern Pondok Darussalam Gontor Education through various activities both academic and non-academic. Finally, this research shows that the ideal pesantren leader is the one who is able to realize the goals of pesantren through the process and system of education in pesante, so that pesantren still exist and are able to prove themselves capable of becoming a reference institution in the future.